Infection-associated non-Hodgkin lymphomas. (November 2015) - Suarez, F.; Lecuit, M.
Abstract: Non-Hodgkin lymphomas (NHLs) are malignant proliferations of lymphoid cells. Lymphoid cells proliferate in a physiological manner in response to antigen-dependent and antigen-independent signals. Some lymphotropic viruses, such as Epstein–Barr virus and human T-lymphotropic virus 1, as well as pathogens leading to chronic antigenic stimulation (such as Helicobacter pylori and hepatitis C virus), are associated with NHL. We review here some of the pathophysiological features of infection-associated NHL.